Designing High-Performance Dual-Ion Batteries at High-Voltage: Challenges, Strategies, and Prospects - Han, Chong; Xu, Yan‑Song; Hu, Ziyang; Cao, An‑Min; Chen, GuanHua (Nano-Micro Letters, 2026)
Dual-ion batteries (DIBs) have emerged as a promising next-generation energy storage technology with compelling advantages induced by anion intercalation mechanism, including high operating voltage (> 4.8 V), abundant raw materials of dual-carbon electrodes, intrinsic electrode safety, and environmental friendliness. However, this mechanism at the cathode side leads to new challenges different from conventional lithium-ion batteries, such as high-voltage electrolyte decomposition, solvent co-intercalation, and limited capacity. In this review, beyond the fundamental understanding and recent progress of DIBs, we systematically discuss their challenges, such as electrolyte decomposition at high voltages, solvent co-intercalation, interfacial instability, asymmetric electrode kinetics, and limited capacity. Corresponding strategies are then summarized, ranging from the design of electrolytes with high oxidation resistance and anion solvation microenvironment regulation to electrode–electrolyte interfacial construction and the discovery of cathode materials with high capacity. The strategies for dynamic matching between cathode and anode, as well as designing more reliable dual-carbon full cells, are further discussed. Finally, prospects for future research are outlined, with emphasis on advanced characterization technologies, theoretical modeling, and rational design of electrode and electrolyte systems. This review provides a roadmap for advancing high-voltage DIBs toward practical applications in large-scale and sustainable energy storage. Highlights: 1 Clarifies fundamental anion intercalation mechanisms, voltage window and solvation microenvironment in high-voltage dual-ion batteries. 2 Systematically identifies key challenges: electrolyte decomposition, solvent co-intercalation, unstable interphases, kinetic mismatch, limited capacity, low-temperature and safety issues. 3 Summarizes electrolyte, electrode, and interfacial engineering strategies and outlines future directions in advanced characterization, theory and artificial intelligence-guided materials/electrolyte design for practical dual-ion batteries deployment.